Meaning in interaction - Deppermann, Arnulf; De Stefani, Elwys (Interactional linguistics, 2024)
This editorial to the Special Issue on “Meaning in Interaction” introduces to the approach of Interactional Semantics, which has been developed over the last years within the framework of Interactional Linguistics. It discusses how “meaning” is understood and approached in this framework and lays out that Interactional Semantics is interested in how participants clarify and negotiate the meanings of the expressions that they are using in social interaction. Commonalities and differences of this approach with other approaches to meaning are flagged, and the intellectual origins and precursors of Interactional Semantics are introduced. The contributions to the Special Issue are located in the larger field of research.
Online veröffentlicht am 18.03.2024
Gesehen am 15.01.2025